Solution Combustion Synthesis for Various Applications: A Review of the Mixed-Fuel Approach - Samantha Padayatchee; Halliru Ibrahim; Holger B. Friedrich; Ezra J. Olivier; Pinkie Ntola (Fluids)
As solution combustion synthesis (SCS) becomes a universal route to metal oxide nanomaterials, it also paves the way for mixed-fuel combustion synthesis as an advanced approach to the synthesis of materials of desirable properties for diverse applications. Major significance is attached to the rates of decomposition and combustion temperatures of the fuel as determinant factors of the morphology and physicochemical properties of the materials obtained. This has promoted the use of mixed-fuel systems characterized by lower decomposition temperatures of organic fuels and higher rates of combustion. The review work presented herein provides a comprehensive analysis of the applications of mixed-fuel SCS in ceramics, fuel cells, nanocomposite materials, and the recycling of lithium battery materials while taking into consideration the effects of the mixed-fuel system on the physicochemical and morphological properties of those materials, as compared to their analogues prepared via single-fuel SCS.